Contribution of Logical Thinking Ability to Students’ Achievement in Three Level of Representations in Chemical Dynamic Materials - Rakhmawan, Aditya; Firman, Harry; Redjeki, Sri; Mulyani, Sri (Jurnal Penelitian dan Pembelajaran IPA, 2018)
This research aims to explore information about the profile of the ability of logical thinking of high school students and its effect on student achievement on three levels of representation of chemical dynamics material. This research uses a non-experimental as research design in form of survey. This research involving 242 persons of 11 grade high school students at Ketapang Regency, West Borneo Province. Sampling is done by purposive sampling as a sampling method. There are two instruments in this research, first is Test of Logical Thinking and second is Test of three levels of representations that including 25 multiple choice tests which consist of three levels of representations such as macroscopic, submicroscopic, and symbolic levels. The material raised in this test is chemical dynamics material, including the concepts of reaction rates and chemical equilibrium. The research results is based on the statistically tested findings using the Pearson correlation test, it was found that logical thinking ability had a significant effect on macroscopic, submicroscopic, and symbolic with correlation coefficients of 0.352, 0.684, and 0.564, and significance values is less than 5% each of them.